SPECIAL PROBLEMS IN OIL AND GAS SEPARATION - Sirojiddinov Akhrorjon Mansurjon ogli, (PEDAGOGS, 2025)
Annotation. Oil and gas produced from wells are normally complex mixtures of hundreds of different compounds. A typical well stream is a turbulent mixture of oil, gas, water, and sometimes solid particles. The well stream should be processed as soon as possible after bringing it to the surface. Field separation processes fall into two categories: (1) separation of oil, water, and gas; and (2) dehydration that removes condensable water vapor and other undesirable compounds, such as hydrogen sulfide or carbon dioxide.